A novel β-lactam-aminoglycoside combination in veterinary medicine: The couse of ceftiofur and gentamicin to combat resistant Escherichia coli - CENGIZ, M.; SAHINTURK, P.; HEPBOSTANCI, G.; AKALIN, H.; SONAL, S. (Journal of the Hellenic Veterinary Medical Society, 2020)
The focus of this study was to evaluate the efficacy of ceftiofur+gentamicin combination to increase the success of antimicrobial inhibition against resistant Escherichia coli (E.coli) strains isolated from animals. Interaction between drugs was determined using checkerboard method and the fractional inhibitory concentration index was interpreted as synergism, antagonism and indifference. The combination was defined as bactericidal or bacteriostatic based on the minimum bactericidal test results. Mutant prevention concentration test was used to evaluate the resistance tendency suppression potential of the combination. The synergistic effect was detected for all E. coli strains by the checkerboard method; even the strains that were resistant to the individual compounds in the combination. Based on the results of minimum bactericidal concentration test, the combination exhibited bactericidal effect against all E. coli strains. In addition, the individual mutant prevention concentrations of ceftiofur and gentamicin decreased up to 125-fold by using the combination for the inhibition of resistant E. coli strains. The results indicated that killing potential of co-use of the compounds is much stronger than their individual use. The combination achieved to decrease the mutant prevention concentrations and this can reduce the risk of emergence of single mutations during treatment done with suggested doses.